Variação na estrutura das comunidades microbianas associadas à infecção por Haemonchus contortus em ovelhas Morada Nova - Silva, Weslley dos Santos (Universidade Federal de São Carlos, 2023)
Morada Nova is a breed of wool sheep adapted to the tropical climate of the country and which have aptitude related to the production of meat and leather. Gastrointestinal nematode infections represent one of the most critical problems in sheep production, aggravated by the increase in resistance due to the indiscriminate use of anthelmintic drugs. The present work aimed to identify microbiological markers in the feces and in the rumen content of sheep with high and low parasitic load of the nematode Haemonchus contortus, through network correlation approaches. Extreme lambs in terms of high (N=11) and low (N=10) parasite load were selected after two parasitological challenges by artificial infection with infective larvae of H. contortus. Samples of feces and rumen contents were collected and sequenced for bacterial 16s rRNA coding genes. Analysis of the correlation network, performed using the WGCNA software, identified one module of amplicon sequence variants (ASV) in feces and two modules of ASVs in ruminal contents. The modules identified in both environments are significantly associated with high parasitic load. The results obtained highlight the presence of Prevotella sp., Treponema sp., Fibrobacter sp., Shuttleworthia sp. and the family Bacteroidales BS11 intestinal group as microorganisms potentially involved in energy availability after infection by H. contortus, given that these microorganisms act in the degradation of cellulosic matter in ruminant animals. Butyrate, product of cellulosic digestion by Shuttleworthia sp. and Prevotellaceae UCG-001 sp., has potential influence on the modulation of the immune system due to its anti-inflammatory role. In addition, mucin has a possible influence on the control of gastrointestinal nematode (GIN) infection and is related to the genus Akkermansia. Our results allow a better understanding of microorganisms that may be involved in determining the phenotype in Morada Nova sheep and suggest potential microorganisms as targets for interventions or as markers of H. contortus infection.
Variation in the structure of microbial communities associated with Haemonchus contortus infection in Morada Nova ewes
Keywords: Nematóides; Nematodes; Butirato; Butyrate; Ácidos graxos de cadeia curta; Short-chain fatty acid; Mucina; Mucin; CIENCIAS BIOLOGICAS::GENETICA